DUAL-STAGE IDENTIFYING DATA OF ARM ROBOT FOR RECOGNIZING AND SORTING OBJECTS WITH DOUBLE FACES PERMITTED-PROHIBITED AREA - Sendari, S.; Rahmawati, Y.; Rahmawati, H.; Zaeni, I.A.E.; Tibyani, T.; Khoirurizka, N.; Shodiq, M.A.F.; Wibowo, D.A.; Mokhtar, N.B.; Lin, H. (Journal of Advanced Manufacturing Technology (JAMT), 2024)
When relocating objects to specific directions, sometimes a particular object is surrounded by another object with directions, such as upper or bottom parts. The objective of the arm robot is to take appropriate actions for changing situations in the workspace, such as which object should be picked up and where it should be relocated to the proper locations when any other objects surrounding the object have specific directions to be followed. This paper studies a dual-stage identifying data of an arm robot for recognizing and sorting objects. Furthermore, the dual-stage identifying data was evaluated with experimental conditions, where several pawns and pictures of snakes and ladders represent objects in a workspace. The arm robot is observed while it successfully grabs and relocates a particular pawn to the appropriate location according to the situations affected by the positions of the snake and ladder pictures. The experimental results show that the arm robot with dual-stage identifying data successfully informs the workspace conditions to relocate a particular pawn to a new location.